Synergy between Sharia Trade Financing and Indonesian Economic Diplomacy in Enhancing Intra-OIC Trade - abdulmajid; Hozinul Asror; Nur Kholis (International Journal of Economics Accounting and Management, 2025)
This study aims to analyze the synergy between Islamic trade financing and Indonesia's economic diplomacy in strengthening intra-Organization of Islamic Cooperation (OIC) trade. Although various Islamic economic initiatives have been launched through the Islamic Development Bank (IsDB) and the International Islamic Trade Finance Corporation (ITFC), the level of economic integration among OIC member countries remains relatively low, with intra-OIC trade accounting for only 16–17% of the total global trade of member countries. This condition indicates a gap between the financial potential of Islamic financial institutions and the effectiveness of national economic diplomacy policies. This study uses a qualitative approach through a literature review to explore academic literature, policy documents, and reports from Islamic financial and diplomatic institutions. The results of the analysis show that sharia trade financing plays an important role in supporting trade flows between Muslim countries through financial instruments such as murabahah, istisna, and wakalah bil ujrah, but its impact is still limited without the support of proactive economic diplomacy. Furthermore, Indonesia's economic diplomacy focuses on promoting halal products and multilateral cooperation, but it has not been effectively integrated with existing sharia financing schemes. This study recommends developing an Islamic Economic Diplomacy model that incorporates financial and diplomatic dimensions into a single policy framework, emphasizing three main pillars: institutional coordination, integration of financing and trade promotion, and strengthening of value-based diplomacy based on maqāṣid al-sharī‘ah. This synergy is expected to enhance intra-OIC trade competitiveness, expand the global halal value chain, and position Indonesia as the center of gravity for a just, inclusive, and sustainable global Islamic economy.